PENGARUH KONSUMSI IKAN DAN KERANG TERHADAP KADAR Pb DARAH MANUSIA, STUDI KASUS DI KELURAHAN SUKOLILO, KENJERAN, SURABAYA - Muhammad Arief (Jurnal Perikanan Universitas Gadjah Mada, 2005)
The industrial and domestic waste containing heavy metal contaminate river and the sea. Through bioacumulation process, contaminant was absorbed by aquatic organisms such as fish, shellfish and shrimp. The aim of this research was to identify the influence of fish and shellfish consumption on lead concentration in blood of people who consumed fish and shellfish. Human blood samples were taken as specimens in this research. Maximum level of lead permitted by World Health Organization (WHO) in human blood is 80 mg/100 ml. Samples of human blood, fish, shellfish, and sea water were taken from two locations of fisher groups, i.e. from Sukolilo subdistrict, district of Kenjeran, Surabaya, and from Lobuk village, district of Sumenep, Madura. Lead concentration in the samples were analyzed by AAS (Atomic Absorbent Spectrophotometer) method. Data were subjected for t-test analysis. Results showed that lead concentration in women blood living in Sukolilo (Kenjeran,Surabaya) and Labuk village (Sumenep, Madura) were significantly different, while the mean level of lead in human blood in Sukolilo was higher than that in Labuk village. In Sukolilo, consumption of fish and shellfish had a major contribution to the level of lead in human blood.